Digital video coding standards and their role in video communications - Schafer, R.; Sikora, T. (Proceedings of the IEEE, 1995)
The efficient digital representation of image and video signals has been subject of considerable research over the past 20 years. With the growing availability of digital transmission links, progress in signal processing, VLSI technology and image compression research, visual communications has become more feasible than ever. Digital video coding technology has developed into a mature field and a diversity of products has been developed-targeted for a wide range of emerging applications, such as video on demand, digital TV/HDTV broadcasting, and multimedia image/video database services. With the increased commercial interest in video communications the need for international image and video coding standards arose. Standardization of video coding algorithms holds the promise of large markets for video communication equipment. Interoperability of implementations from different vendors enables the consumer to access video from a wider range of services and VLSI implementations of coding algorithms conforming to international standards can be manufactured at considerably reduced costs. The purpose of this paper is to provide an overview of today's image and video coding standards and their role in video communications. The different coding algorithms developed for each standard are reviewed and the commonalities between the standards are discussed.< >